2003
DOI: 10.2307/4003831
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Off-Stream Water Developments to Improve Riparian Grazing

Abstract: Livestock grazing in riparian areas is an important management issue on both private and public lands. A study was initiated in northeastern Oregon to evaluate the economic and ecological impacts of different cattle management practices on riparian areas. The effect of off-stream water and salt on livestock distribution and subsequent impact on riparian use, water quality, and livestock production was evaluated. A multi-period bioeconomic linear programming model is used to evaluate the long-term economic feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Recent analyses conducted by Stillings et al (2003) showed that off-spring water developments and salt placement could potentially increase expected annual net returns by $4 500-$11 000 for a 300-head cow-calf operation using public lands with typical riparian area management considerations.…”
Section: Modification Of Abiotic Factorsmentioning
confidence: 99%
“…Recent analyses conducted by Stillings et al (2003) showed that off-spring water developments and salt placement could potentially increase expected annual net returns by $4 500-$11 000 for a 300-head cow-calf operation using public lands with typical riparian area management considerations.…”
Section: Modification Of Abiotic Factorsmentioning
confidence: 99%
“…Increases to in-channel and riparian vegetation cover were likely due to a more even livestock distribution in BMP pastures (Porath et al 2003;Stillings et al 2003) which often results in increased upland forage consumption, weight gains, and ranch profits (Porath et al 2002;Stillings et al 2003), while providing ecological benefits (Fleischner 1994;Chambers et al 2004). Because of the nature of nNDVI calculation (i.e., R DnNDVI¼0), the decreased values observed in non-BMP pastures do not necessarily correspond with reduced in-channel vegetation cover, but may also be due to a proportionally lower increase than in BMP pastures.…”
Section: Discussionmentioning
confidence: 97%
“…Although eliminating direct livestock access to streams with riparian exclosures has been advocated by some, this method removes an important source of livestock forage (Stillings et al 2003), especially in semiarid and arid regions (Ehrhart and Hansen 1997). Moreover, doing so is often impractical, costly, and undesirable to livestock producers (Godwin and Miner 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Stillings et al 2003;Agouridis et al 2005). However, economic benefits are also available to producers in using this foragerich environment (Unterschultz et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…While the environmental impacts of riparian area BMPs are well documented, limited information is available for these types of practices in terms of direct farmlevel economic impacts of adoption. Stillings et al (2003) and Yang and Weersink (2004) estimate the economic impacts of establishing off-stream watering sites and riparian buffers, respectively, but neither study examines adoption for producers in the Canadian Prairie region. Unterschultz et al (2004) provide a farm-level economic analysis of riparian buffers and off-stream watering, but only for native range in southwestern Alberta.…”
Section: Introductionmentioning
confidence: 99%